Research on the Optimization and Risk Control Strategies of Financial Audit Process in Universities: An Analysis Based on the Perspective of Internal Control - Tan, Junjia; Chen, Fang (International Journal of Global Economics and Management, 2024)
This study starts from the perspective of internal control, exploring the optimization of financial audit processes and risk control strategies in universities. Through comprehensive measures such as policy systems, personnel training, and information construction, a risk control guarantee system has been established, improving audit efficiency and quality. The study emphasizes that in the digital age, it is necessary to introduce technologies such as intelligent RPA and big data analysis to achieve automated processing and real-time monitoring of financial data. The research results provide strong support for university financial management and suggest that universities should adopt innovative technologies, strengthen international cooperation, and promote the modernization and intelligence of financial management.